The addition of alpha-ketoglutarate to NT-proBNP improves the prediction of long-term all-cause mortality in acute heart failure patients - Tianyu Xu; Hao Zhang; Zhengliang Peng; Yuli Huang; Qiong Zhan; Zhuang Ma; Xianghui Zeng; Chen Liu; Qingchun Zeng; Yugang Dong; Dingli Xu (Annals of Medicine)
Background and Objective Alpha-ketoglutarate (AKG), is a major intermediate metabolite of the tricarboxylic acid cycle, and is closely associated with cardiometabolic disease prognosis. Previous studies indicated that AKG is related to myocardial energy expenditure levels and reflects adverse short-term outcomes in heart failure (HF) patients. In this prospective cohort study, we examined the long-term prognostic value of AKG levels in acute HF (AHF) patients.Methods Plasma AKG levels were assessed in patients hospitalized with AHF. Hazard ratios (HRs) and 95% confidence intervals (CIs) for all-cause mortality were calculated via multiple Cox regression. All-cause mortality was compared between patients with NT-proBNP < 1000 pg/ml and those with NT-proBNP ≥ 1000 pg/ml via subgroup analysis.Results Patients with AKG ≥ 9.83 μg/ml had higher heart rates and NT-proBNP and lower left ventricular ejection fraction (LVEF) and systolic blood pressure (SBP). After multiple adjustment, higher AKG was associated with an increased all-cause mortality risk (HR = 1.078, p < 0.001). Compared with AKG < 9.83 μg/ml, AKG ≥ 9.83 μg/ml nearly doubled (HR = 1.929, p < 0.001) and quadrupled (HR = 4.160, p < 0.001) the all-cause mortality risk in patients with NT-proBNP ≥ 1000 pg/ml and those with NT-proBNP < 1000 pg/ml, respectively.Conclusions and Relevance Plasma AKG was independently associated with greater all-cause mortality risk in patients with AHF. Higher AKG levels retained prognostic value for patients with relatively low NT-proBNP.